INFLUENCE OF OPTICAL PHONON CONFINEMENT ON TWO-PHONON CAPTURE PROCESSES IN QUANTUM DOTS - Vartanyan, A.I.; Mughnetsyan, V.N.; Vardanyan, K.A.; Dvurechenskii, A.V.; Kirakosyan, A.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2014)
Electron capture process in GaAs/AlAs spherical quantum dot-quantum well structure is studied theoretically. The capture rate in two polar-optical-phononmediated capture processes has been calculated by taking into account the phonon confinement effect. Carrier capture is shown to proceed with rates as high as 1010 s–1 at temperature T>100 K. A short capture time is also achieved for low carrier density.
Keywords: capture process, two-phonon processes, confined optical phonons